IMPACT OF SOCIAL AND CULTURAL ASPECTS ON THE DEVELOPMENT OF THE EDUCATION SYSTEM (International Journal of Food and Nutritional Sciences, 2022)
If education fails to improve people's lives and make society more civilized, then it has failed in its primary aim and is useless. When it comes to making lasting changes in oneself, nothing is more effective than a good education. Three hundred and seventy students in their first and last years of college participated in the research. There were 283 total responders, with 75 men and 208 females participating. Impact of Social and Cultural Aspects on the Development of the Education System. Descriptive statistics, including frequency counts and mean scores, were used to the data obtained in order to shed light on the study's hypotheses and findings. According to the results of this research, students' experiences and interactions benefit greatly by exposure to other cultures. Students' experiences are more influenced by social-cultural learning than by their interactions with one another. The findings of this research help pave the way for the incorporation of sociocultural and E-Learning perspectives into the area of literary instruction. It also provides a fresh perspective on the factors that shape students' experiences and interactions in the classroom. In sum, education is crucial to improving one is standard of living. Because education plays such a crucial role in directing a person's life.